Genome-Wide Association Study of Response to Selenium Supplementation and Circulating Selenium Concentrations in Adults of European Descent. Issue 2 (31st December 2020) - Batai, Ken; Trejo, Mario J; Chen, Yuliang; Kohler, Lindsay N; Lance, Peter; Ellis, Nathan A; Cornelis, Marilyn C; Chow, H-H Sherry; Hsu, Chiu-Hsieh; Jacobs, Elizabeth T
ABSTRACT: Background: Selenium (Se) is a trace element that has been linked to many health conditions. Genome-wide association studies (GWAS) have identified variants for blood and toenail Se levels, but no GWAS has been conducted to date on responses to Se supplementation. Objectives: A GWAS was performed to identify the single nucleotide polymorphisms (SNPs) associated with changes in Se concentrations after 1 year of supplementation. A GWAS of basal plasma Se concentrations at study entry was conducted to evaluate whether SNPs for Se responses overlap with SNPs for basal Se levels. Methods: A total of 428 participants aged 40–80 years of European descent from the Selenium and Celecoxib Trial (Sel/Cel Trial) who received daily supplementation with 200 µg of selenized yeast were included for the GWAS of responses to supplementation. Plasma Se concentrations were measured from blood samples collected at the time of recruitment and after 1 year of supplementation. Linear regression analyses were performed to assess the relationship between each SNP and changes in Se concentrations. We further examined whether the identified SNPs overlapped with those related to basal Se concentrations. Results: No SNP was significantly associated with changes in Se concentration at a genome-wide significance level. However, rs56856693, located upstream of the NEK6, was nominally associated with changes in Se concentrations after supplementation ( P  = 4.41 × 10 −7 ), as were 2 additional SNPs, rs11960388 and rs6887869, located in the dimethylglycine dehydrogenase ( DMGDH )/betaine-homocysteine S-methyltransferase ( BHMT ) region ( P  = 0.01). Alleles of 2 SNPs in the DMGDH / BHMT region associated with greater increases in Se concentrations after supplementation were also strongly associated with higher basal Se concentrations ( P  = 8.67 × 10 −8 ). Conclusions: This first GWAS of responses to Se supplementation in participants of European descent from the Sel/Cel Trial suggests that SNPs in the NEK6 and DMGDH / BHMT regions influence responses to supplementation.